Aspergillus march: from ABPA to aspergilloma to subacute invasive aspergillosis. Issue 1 (December 2016) - Dogra, Vikas; Sinha, Ankit; Saxena, Rajat; Talwar, Deepak
Abstract Background Aspergillus is a ubiquitous fungus responsible for allergic as well as saprophytic and invasive manifestations depending on host's immune status. The following case report demonstrates progression of allergic manifestations ofAspergillus to its invasive form in an individual with decreasing immunity. This can lead to uncertainties in diagnosis and management. Case presentation A 28-year-old male, non smoker, known case of ABPA (allergic bronchopulmonary aspergillosis) was admitted with complaints of cough for 1 month, associated with recurrent episodes of hemoptysis for last 5 days. CT Thorax revealed homogenous dense round opacity in right upper lobe which replaced previous fibrocalcific bronchiectatic lesion with cavity and aspergilloma, bulging across the major fissure with fibrotic strands extending to periphery in all directions. Post-pneumonectomy microscopic examination revealedAspergillus hyphae invading blood vessels. Conclusion There is a need for close clinical and radiologic follow up of patients withAspergillus and our patient demonstrated overlap of complete spectrum ofAspergillus disease with march from one end to the other end.